Critical Care Nurses' Experiences Caring for Patients When Relatives Were not Allowed in the ICUs due to COVID-19 Pandemic - Lina Stenman RN, CCN, Msc; Lisa Högberg RN, CCN, Msc; Åsa Engström RN, CCN, PhD (SAGE Publishing, 2022)
Introduction Health care workers faced new challenges during the COVID-19 pandemic when physical contact with relatives more or less disappeared. Objectives The aim of this study is to describe the experiences of critical care nurses (CCNs) working in intensive care units (ICUs) under the visiting restrictions imposed as a result of COVID-19. Method This study followed a qualitative design. The purposive sample included CCNs with at least 1 year of experience working in an ICU with a visiting policy affected by the pandemic. Data collection was carried out via semi-structured interviews and analyzed through a qualitative content analysis with an inductive approach. Results The study results are presented in three categories with 10 subcategories. CCNs value the presence of patients' relatives at the bedside and described many challenges when relatives could not be present with the patient during the pandemic. Conclusion Close relatives are able to share essential information about the patients and provide much-needed emotional support to them, the relatives' role is of central importance and CCNs value their presence in ICUs more than any positive consequences of them not being there.